An Urban Rainfall Storm Flood Severity Index - Jobin, Erik (Université d'Ottawa / University of Ottawa, 2013)
Extreme rainfall statistics are important for the design and management of the water resource infrastructure. The standard approach for extreme rainfall event severity assessment is the Intensity-Duration-Frequency (IDF) method. However, this approach does not consider the spatial context of rainfall and consequently does not properly describe rainfall storm severity, nor rarity. This study provides a critical account of the current standard practice and presents an approach that takes into consideration both the spatial context of rainfall storms, and indirectly incorporates runoff to produce a representative approach to assessing urban rainfall storm severity in terms of flood potential. A stepwise regression analysis was performed on a dataset of individual rainfall storm characteristics to best represent documented basement floodings in the City of Edmonton. Finally, the urban rainfall storm flood severity index was shown to be most representative of the documented basement floodings' severity when compared to that of the IDF method.
Keywords: extreme; extreme rainfall; extreme rainfall storm; rainfall storm; extreme rainfall statistics; flooding; IDF; intensity-duration-frequency; storm severity; rainfall severity; rainfall storm severity; storm severity index; extreme rainfall event; rainfall event; severity assessment; spatial rainfall; weather radar; radar; precipitation; rainfall; City of Edmonton; Edmonton; Canada; extreme event; extreme rainfall event; extreme storm; rainfall event; runoff; basement flooding; basement flood; flood; urban rainfall storm severity; urban rainfall storm flood severity index; flood potential; stepwise regression; rainfall storm characteristics